2024
DOI: 10.1590/1519-6984.259217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of insect pests on maize crop in District Mansehra, Khyber Pakhtunkhwa, Pakistan

Abstract: The maize crop is used as food for humans, livestock and poultries forms, it is also used in bread making, corn flakes, corn syrup, corn starch and corn oils. The field study consisted of one experimental trial, about the incidence of that insect pest complex on maize cultivar Azam during the Kharif season 2020 at the Agricultural, Research Station, Baffa, Mansehra. The trial was laid out in the Randomized Complete Block Design (RCBD), and then it was divided into three replications. The result obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
4
4
0
Order By: Relevance
“…Furthermore, the population levels of D. maidis per plant in our study were similar to the results found by Virla et al 35 . On the other hand, a study carried out by Khan et al 36 . in the Hazara division, Khyber Pakhtunkhwa, Pakistan, found an average density per corn season of 1.33 adults of D. maidis per plant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the population levels of D. maidis per plant in our study were similar to the results found by Virla et al 35 . On the other hand, a study carried out by Khan et al 36 . in the Hazara division, Khyber Pakhtunkhwa, Pakistan, found an average density per corn season of 1.33 adults of D. maidis per plant.…”
Section: Resultssupporting
confidence: 91%
“…[32][33][34] Therefore, resource quality is lost in the final plant development stage, potentially harming D. maidis populations. Furthermore, the population levels of D. maidis per plant in our study were similar to the results found by Virla et al 35 On the other hand, a study carried out by Khan et al 36 in the Hazara division, Khyber Pakhtunkhwa, Pakistan, found an average density per corn season of 1.33 adults of D. maidis per plant. This result was significantly superior to the results found in our study.…”
Section: Dynamic Of Insect and Disease Incidencesupporting
confidence: 91%
“…For these reasons, the leading role of Lepidoptera pests as maize consumers shows that Lepidoptera constitutes the most significant arthropod pests of maize in this region. This pattern is well documented form studies in many maize growing regions of the world (Amudavi et al, 2008;Suckling et al, 2017;Khan et al, 2022).…”
Section: Plant Food Sources In Arthropod Pest Dietssupporting
confidence: 55%
“…Contrastingly, despite consuming lower proportions of maize when compared to the case for Lepidoptera, Hemiptera, and Coleoptera pests exhibited nearly proportionate trophic linkages across the range of three plant food resources. This further underscores the relatively higher threat that Lepidoptera herbivores pose to maize as compared to most coleopteran and hemipteran pests (Khan et al, 2022). It also indicates the relatively lower herbivory risk that Lepidoptera pose to farmland legumes and forest plants in this region.…”
Section: Plant Food Sources In Arthropod Pest Dietsmentioning
confidence: 76%
“…Maize face disruptions during their growth stages, primarily due to small animals referred to as pests, which interfere with plant growth by feeding on them. Common pests affecting maize farming include stem borers, leafhoppers, cob borers, and thrips [8]. Pests are known to attack plants throughout both vegetative and generative growth phases [9].…”
Section: Introductionmentioning
confidence: 99%